Impact of Computer Application in Teaching and Learning at Higher Education in Nepal - Manihar , Abdul Hak (Patan Prospective Journal, 2024)
This paper analyzes the role of computer as a technology in accelerating the efficiency and effectiveness of teaching and learning activities accomplished in the undergraduate and postgraduate educations. The article has employed the secondary data to assess the impact of the computer application in the Nepalese education system. The research done by exploring the pervasiveness of the technologies especially the computer—the latest advancement in science and information-will examine the other relevant elements as used in the higher education. With ICT, things may be created, processed, stored, shown, and shared. Numerous technologies exist, including computers, televisions, and mobile phones, data via electronic media etc., but videoconferencing, blogs, and email are seen as technology-related tools and services.